2017
DOI: 10.1093/beheco/arx039
|View full text |Cite
|
Sign up to set email alerts
|

Nest-box temperature affects clutch size, incubation initiation, and nestling health in great tits

Abstract: Seasonal organisms use temperature as a cue in reproductive decisions, but the role of climate change is not yet clear. Here, an experimental increase in temperature during laying in a small passerine bird reveals that heated females adjusted their incubation behavior and the number of eggs laid, and produced nestlings of equal condition over the season, unlike control females. A small temperature increase may therefore influence breeding strategy and offspring phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 54 publications
0
31
1
Order By: Relevance
“…A third study finds that a treatment that features a sharp increase in temperatures (Schaper et al ) advances lay date. Experiments with nest box warming in great tits find no effect of temperature on lay date (Nager and Vannoordwijk ) but show that birds in warmed nest boxes are less likely to delay incubation onset (Bleu et al ). Studies in blue tits and zebra finches find that females in warmed nest boxes are less likely to skip a day of laying (Yom‐Tov and Wright , Salvante et al ) and advance clutch initiation (Salvante et al ).…”
Section: Part 2 Effects Of Non‐photic Cues On Reproductive Timingmentioning
confidence: 99%
“…A third study finds that a treatment that features a sharp increase in temperatures (Schaper et al ) advances lay date. Experiments with nest box warming in great tits find no effect of temperature on lay date (Nager and Vannoordwijk ) but show that birds in warmed nest boxes are less likely to delay incubation onset (Bleu et al ). Studies in blue tits and zebra finches find that females in warmed nest boxes are less likely to skip a day of laying (Yom‐Tov and Wright , Salvante et al ) and advance clutch initiation (Salvante et al ).…”
Section: Part 2 Effects Of Non‐photic Cues On Reproductive Timingmentioning
confidence: 99%
“…Many studies have explored the effects of climate change on avian communities, specifically regarding shifts in reproductive phenology (Brawn 1991;Bradley et al 1999;Dunn and Winkler 1999) and migration phenology (Cotton 2003), and show varying results. Some studies show that bird populations adjust phenology traits in response to local environmental changes (Bleu et al 2017;Clermont et al 2018). Large-scale studies and metaanalyses have shown a general trend in advancement in the breeding phenology of many bird species over time (Dunn and Winkler 1999;Torti and Dunn 2005;Gordo and Sanz 2006;Radchuk et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…; Bleu et al . ). For example, we have recently shown (using the same nest box design as utilized in this study) that the growth rate of Crimson Rosella ( Platycercus elegans ) nestlings was related to natural variation in temperature mean and extremes within the nest box (Larson et al .…”
Section: Introductionmentioning
confidence: 97%
“…Despite some potential benefits, animals choosing nest boxes could find themselves caught in an ecological trap, due to deleterious microclimate profiles compared to natural hollows (Isaac et al 2008b;Goldingay & Stevens 2009;Maziarz et al 2017;Rowland et al 2017). Even quite small variation in internal nest temperature can have important effects on reproductive performance, behaviour and development in birds (Perez et al 2008;Ardia et al 2010;Bleu et al 2017). For example, we have recently shown (using the same nest box design as utilized in this study) that the growth rate of Crimson Rosella (Platycercus elegans) nestlings was related to natural variation in ECOLOGICAL MANAGEMENT & RESTORATION VOL 19 NO 1 JANUARY 2018 temperature mean and extremes within the nest box (Larson et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation